Pre-heat treatment method of TC4 titanium alloy

CN122959650APending Publication Date: 2026-10-23CHENGDU ADVANCED METAL MATERIALS IND TECH RES INST CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611333827.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

上述过度粗化的片层组织以及数量不足或稳定性过高的残余β相,均不利于材料冷变形塑性的提高

Benefits of technology

一、本发明采用930~950℃保温后随炉冷却至680~720℃再强风冷的分段冷却路径,而不是从高温保温温度直接强风冷。随炉缓冷阶段促进高温β相发生扩散型转变,有效抑制大量针状α′马氏体形成。本发明在680~720℃终止炉冷,避免持续随炉冷却导致晶内α相片层过度粗化以及残余β相过度分解。在炉冷至680~720℃后采用强风冷,利用适宜的冷却速率保留具有适当机械稳定性的亚稳β相,实现对残余β相含量和稳定性的调控。亚稳β相能够在室温拉伸或冷拉拔过程中发生应变诱导转变,使加工硬化率在初始下降后出现阶段性回升。该相变诱导塑性效应有利于延缓应变局部化、颈缩和裂纹萌生。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122959650A_ABST
    Figure CN122959650A_ABST
Patent Text Reader

Abstract

The present application relates to the field of TC4 titanium alloy preparation process, and more particularly to a pre-heat treatment method for improving plasticity and cold drawing deformation capacity of TC4 titanium alloy, comprising the following steps: a. setting the hot-rolled TC4 titanium alloy in a heat treatment furnace, heating the heat treatment furnace to 930-950 DEG C and keeping for 20-40 min; b. after the keeping, cooling the TC4 titanium alloy in the heat treatment furnace to 680-720 DEG C; c. then, taking the TC4 titanium alloy out of the heat treatment furnace and cooling to room temperature by strong wind. The present application is suitable for the pre-heat treatment process of TC4 titanium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of TC4 titanium alloy preparation process, and in particular to a preheating treatment method for TC4 titanium alloy. Background Technology

[0002] TC4 titanium alloy is a typical α+β type two-phase titanium alloy, characterized by high specific strength, good corrosion resistance, and excellent comprehensive mechanical properties. It is widely used in aerospace, shipbuilding, medical devices, energy equipment, and high-end fasteners. The heat treatment of TC4 titanium alloy typically involves hot rolling, annealing, surface treatment, cold drawing, and intermediate annealing to obtain the target dimensions, surface quality, and mechanical properties.

[0003] Taking Chinese patent CN120210703A as an example, it relates to a method for improving the strength of TC4 titanium alloy wire. The method includes the following steps: (1) Martensitization treatment: heating the TC4 titanium alloy wire to a temperature range of 800℃~850℃ and holding it therefore, and then water quenching it to obtain α+α ′ (1) Initial martensitic structure; (2) Fiberization treatment: The TC4 titanium alloy wire from step (1) was drawn with moderate strain to obtain fibrous α+α ′ (3) Martensite decomposition treatment: The TC4 titanium alloy wire from step (2) is heated to a temperature range of 500℃~600℃, held for a short time and then air-cooled to allow α+α ′ Fiberous tissue decomposes into α+(α s +β) Multiphase fibrous structure; (4) Non-continuous cumulative large strain drawing based on defect rearrangement treatment: The TC4 titanium alloy wire from step (3) is subjected to non-continuous, multiple small strain drawing to achieve cumulative large strain drawing, and the wire is heated to 400℃~500℃ between adjacent passes for defect rearrangement treatment; finally, high-strength TC4 titanium alloy wire is obtained.

[0004] This heat treatment method employs water quenching in step (1) to facilitate the diffusionless martensitic transformation of the high-temperature β phase, forming needle-like α phases. ′ Martensite. Acicular α ′ Martensite possesses high hardness and strength, which increases resistance to subsequent cold deformation and reduces elongation and reduction of area. Especially during direct water quenching, a large amount of the high-temperature β phase transforms into needle-like α phase during the cooling stage. ′Martensite formation makes it difficult to reasonably control the content and stability of the metastable β phase, which plays a role in subsequent cold deformation. However, if natural air cooling is used, the high-temperature β phase can undergo a certain degree of diffusion-type decomposition, forming grain boundary α phase, intragranular lamellar α phase, and residual β phase. However, natural air cooling has limited ability to regulate the content and mechanical stability of the residual β phase, and the resulting microstructure may not generate sufficient phase transformation-induced plasticity during cold deformation. In addition, if the cooling process is only continuous furnace cooling to a lower temperature, the high-temperature β phase will undergo further diffusion-type decomposition, the intragranular α phase lamellars will gradually coarsen, and the content of the residual β phase will decrease. At the same time, β-stabilizing elements such as V may further enrich the residual β phase, increasing the stability of the remaining β phase. The above-mentioned excessively coarsened lamellar structure and insufficient quantity or excessively high stability of the residual β phase are all detrimental to improving the cold deformation plasticity of the material. Therefore, achieving regulation and control of the α phase morphology, residual β phase content, and residual β phase stability in TC4 titanium alloy is the key to improving the material's plasticity and cold drawing deformation capability. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a preheating treatment method for TC4 titanium alloy to improve the plasticity and cold drawing deformation ability of TC4 titanium alloy.

[0006] The technical solution adopted by this invention to solve its technical problem is a pre-heat treatment method for TC4 titanium alloy, comprising the following steps: a. placing the hot-rolled TC4 titanium alloy in a heat treatment furnace, heating the furnace to 930°C to 950°C, and holding it at that temperature for 20 to 40 minutes; b. after holding, cooling the TC4 titanium alloy in the furnace to 680°C to 720°C; c. subsequently, removing the TC4 titanium alloy from the heat treatment furnace and cooling it to room temperature with strong air. In the heat treatment process, the hot-rolled TC4 titanium alloy is first heated and held in the heat treatment furnace, and then slowly cooled to 680°C to 720°C by furnace cooling. This avoids the formation of a large number of needle-like α-shaped deposits caused by rapid cooling directly from the high-temperature zone. ′ Martensite. Subsequently, the TC4 titanium alloy was removed from the heat treatment furnace and rapidly cooled to room temperature by strong air. This avoids excessive coarsening of the α-phase lamellars and excessive decomposition of the residual β-phase caused by continuous slow cooling. As a result, an appropriate amount of metastable β-phase with suitable mechanical stability is retained in the room temperature microstructure, allowing the metastable β-phase to undergo strain-induced transformation during subsequent cold drawing, thereby improving the material's plasticity and cold drawing deformation capacity.

[0007] Furthermore, the hot-rolled TC4 titanium alloy is in the form of wire, coil, or bar.

[0008] Furthermore, in step c, forced air cooling includes fan-assisted cooling, blower cooling, or compressed gas jet cooling.

[0009] Furthermore, in step a, the heat treatment furnace is heated to 940°C and held for 30 minutes.

[0010] Furthermore, in step b, the TC4 titanium alloy in the heat treatment furnace is cooled to 700°C.

[0011] The beneficial effects of this invention are: I. This invention employs a segmented cooling path: holding at 930–950℃ followed by furnace cooling to 680–720℃ and then forced air cooling, instead of direct forced air cooling from the high-temperature holding temperature. The slow furnace cooling stage promotes the diffusion-type transformation of the high-temperature β phase, effectively suppressing a large number of needle-like α phases. ′ Martensite formation occurs. This invention terminates furnace cooling at 680–720°C to avoid excessive coarsening of the intragranular α-phase lamellars and excessive decomposition of the residual β-phase caused by continuous furnace cooling. After furnace cooling to 680–720°C, strong air cooling is employed, utilizing an appropriate cooling rate to retain the metastable β-phase with suitable mechanical stability, thus achieving control over the content and stability of the residual β-phase. The metastable β-phase can undergo strain-induced transformation during room temperature stretching or cold drawing, causing a phased recovery in the work hardening rate after an initial decrease. This phase transformation-induced plasticity effect helps delay strain localization, necking, and crack initiation.

[0012] Second, this invention does not simply reduce the overall work hardening rate, but rather, while reducing the deformation resistance in the initial stage of cold deformation, utilizes the metastable β phase to provide secondary work hardening capability in subsequent deformation stages, achieving a reasonable match between initial deformation resistance and subsequent uniform deformation capability. It does not primarily aim to improve final service strength, but rather to increase plasticity reserve, improve work hardening behavior, and enhance crack resistance, making it more suitable for cold working of wire rods.

[0013] Third, when using the preferred process of holding at 940℃ for 30 min, furnace cooling to 700℃, and then strong air cooling, the yield strength of the sample was 755 MPa, the tensile strength was 801 MPa, the elongation reached 19.0%, and the reduction of area reached 64%. Both the elongation and reduction of area were higher than those of the hot-rolled state and other comparative cooling processes, indicating that this process can effectively improve the cold drawing deformation capability of TC4 titanium alloy.

[0014] This invention is applicable to the pre-heat treatment process of TC4 titanium alloy. Attached Figure Description

[0015] Figure 1 This is a microstructure diagram of hot-rolled TC4 titanium alloy, which mainly consists of equiaxed primary α phase, acicular secondary α phase, and β phase.

[0016] Figure 2 These are microstructure images of TC4 titanium alloy after different heat treatment processes, in which: Figure 2 (a) Microstructure of the water-quenched sample after heating to 940℃ and holding for 30 min. The microstructure mainly consists of needle-like α-shaped structures. ′ Composed of martensite and β phase; Figure 2 (b) Microstructure of the oil-quenched sample after heating to 940℃ and holding for 30 min. The microstructure mainly consists of needle-like α-shaped structures. ′ Composed of martensite and β phase; Figure 2 (c) Microstructure of the sample heated to 940℃ and held for 30 min, then directly cooled by strong air. The microstructure mainly consists of needle-like α-shaped particles. ′ Composed of martensite, fine lamellar secondary α phase and β phase; Figure 2 (d) is the microstructure of the sample after being heated to 940℃ and held for 30 min and then naturally air-cooled. The microstructure mainly consists of grain boundary α phase, intragranular lamellar α phase and residual β phase. Figure 2 (e) is the microstructure of the sample heated to 940℃ and held for 30 min, then furnace cooled to 700℃ and then strongly air-cooled. The microstructure mainly consists of grain boundary α phase, intragranular lamellar α phase and residual β phase. Figure 2 (f) is the microstructure of the sample heated to 940℃ and held for 30 min, then furnace cooled to 540℃ and then strongly air-cooled. The microstructure is mainly composed of grain boundary α phase, coarse lamellar α phase within the grains and a small amount of residual β phase, showing obvious coarse lamellar structure characteristics.

[0017] Figure 3 These are the engineering stress-strain curves of TC4 titanium alloy after different heat treatment processes. The vertical axis represents engineering stress, and the horizontal axis represents engineering strain.

[0018] Figure 4 The curves show the work hardening rate versus true strain of TC4 titanium alloy after different heat treatment processes. The vertical axis represents the work hardening rate, and the horizontal axis represents the true strain. Detailed Implementation

[0019] The invention will be further described below with reference to the accompanying drawings.

[0020] The pre-heat treatment method for TC4 titanium alloy involves first holding the TC4 titanium alloy at a high temperature in the α+β two-phase region, followed by slow furnace cooling. This allows the material to slowly pass through the furnace, preventing the formation of needle-like α-phase structures that would otherwise result from direct rapid cooling. ′ The martensitic transformation temperature range promotes controlled diffusion-type decomposition of the high-temperature β phase, thereby inhibiting the formation of numerous needle-like α phases. ′Martensite is formed. After the material is cooled in the furnace to a specific medium temperature range, strong air cooling is used to retain the remaining β phase at a suitable cooling rate to room temperature, and to keep at least a portion of the β phase in a metastable state. During subsequent room temperature stretching or cold drawing, the metastable β phase can undergo strain-induced transformation, which delays strain localization and crack initiation through phase transformation-induced plasticity and staged secondary work hardening, thereby improving the elongation, reduction of area, and cold drawing deformation capacity of TC4 titanium alloy wire.

[0021] The present invention adopts the following technical solution: (1) hot-rolled TC4 titanium alloy wire, wire rod or bar for subsequent drawing is placed in a heat treatment furnace, heated to 930℃~950℃, and held for 20 min~40 min; (2) after the holding period, the TC4 titanium alloy wire, wire rod or bar is cooled with the furnace to 680℃~720℃; (3) when the material temperature drops to 680℃~720℃, the TC4 titanium alloy wire, wire rod or bar is taken out of the furnace and cooled to room temperature by strong air. Preferably, the heating temperature in step (1) is 940℃ and the holding time is 30 min. Preferably, the furnace cooling termination temperature in step (2) is 700℃. Preferably, the strong air cooling refers to using a fan to blow air, blow air or compressed gas to cool the material to room temperature at a cooling rate higher than that of natural air cooling. The initial microstructure of the TC4 titanium alloy consists of equiaxed primary α phase, acicular secondary α phase and β phase. After the aforementioned preheating treatment, the microstructure of TC4 titanium alloy mainly comprises grain boundary α phase, intragranular lamellar α phase, and residual β phase. At least a portion of the residual β phase is a metastable β phase capable of undergoing strain-induced transformation during room temperature tensile or cold drawing deformation. During room temperature deformation, the work hardening rate of the TC4 titanium alloy after the aforementioned preheating treatment exhibits a multi-stage variation characteristic of decreasing, rebounding, and decreasing again with increasing true strain.

[0022] The principle of this invention is explained as follows: Through the coordinated control of three stages—high-temperature holding, slow furnace cooling, and strong air cooling in the medium-temperature zone—the morphology of the α-phase, the content of the residual β-phase, and the stability of the residual β-phase in TC4 titanium alloy are regulated. Specifically, when the TC4 titanium alloy is held at 930℃ to 950℃, the original primary α-phase, secondary α-phase, and β-phase undergo redistribution, with some α-phase dissolving into the β-phase, resulting in a high-temperature α+β two-phase state suitable for subsequent phase transformation and cooling path control. If water quenching, oil quenching, or strong air cooling is performed directly after the above high-temperature holding, the high-temperature β-phase will undergo a diffusionless martensitic transformation at a high cooling rate, forming acicular α-phase. ′ Martensite. Needle-shaped α-structures simultaneously form in directly air-cooled samples. ′ Martensite, fine lamellar secondary α and β phases. ′ The formation of martensite increases the local hardness and cold deformation resistance of the material, and has an adverse effect on plasticity.

[0023] This invention does not directly subject the material to forced air cooling after high-temperature holding; instead, it first allows the material to be slowly cooled in the furnace to 680–720°C. During this slow furnace cooling process, the high-temperature β phase gradually undergoes a diffusion-type transformation, precipitating grain boundary α phase and intragranular lamellar α phase. This process makes it easier for the material to form needle-like α phases when subjected to direct rapid cooling. ′ The martensitic transformation zone reduces the subsequent direct conversion to acicular α-forms. ′ High-temperature β phase of martensite, and significantly suppresses a large number of needle-like α phases ′ Martensite formation occurs. When the material temperature drops to 680℃~720℃, if slow cooling continues in the furnace, the intragranular α phase will continue to grow and coarsen, and the residual β phase will continue to decompose, making it difficult to obtain a microstructure suitable for cold deformation. Therefore, this invention terminates furnace cooling in this temperature range and immediately uses strong air cooling to room temperature. Strong air cooling starting from 680℃~720℃ can, on the one hand, suppress further coarsening of the intragranular α phase and continued decomposition of the residual β phase; on the other hand, it can retain a certain amount of β phase to room temperature using a suitable cooling rate, and keep at least a portion of the β phase in a metastable state.

[0024] Therefore, the slow cooling and forced air cooling in this invention have different but complementary functions: (1) The main function of the slow cooling stage is to suppress the needle-like α caused by direct rapid cooling from the high-temperature zone. ′ Martensite is formed and the morphology of the α phase is regulated by diffusion-type phase transformation; (2) The main function of the strong wind cooling stage in the medium temperature zone is to interrupt the further coarsening of the structure and the further decomposition of the β phase, while obtaining the metastable β phase with appropriate mechanical stability. In the initial stage of subsequent room temperature stretching or cold drawing deformation, the material mainly bears plastic deformation through dislocation slip in the α phase and β phase, and the work hardening rate gradually decreases with the increase of strain. When the stress or strain reaches the critical condition for the metastable β phase to transform, the metastable β phase begins to undergo strain-induced transformation, generating new phase interfaces, phase transformation strain and additional dislocations, which causes the work hardening rate to rise again, forming a staged secondary work hardening. This increase in work hardening rate is not an unfavorable overwork hardening, but rather, when the work hardening capacity of the material is about to decay, it provides new hardening capacity through the metastable β phase transformation, suppresses the local high strain area, promotes the transfer of deformation to other areas, and thus delays strain localization, necking and crack initiation.

[0025] The excellent cold working performance obtained by this invention comes from the synergistic effect of the following two aspects: on the one hand, slow cooling in the furnace suppresses a large number of needle-like α-shaped particles. ′Martensite formation is achieved, and excessive coarsening of the α-phase lamellars is avoided by controlling the furnace cooling termination temperature, thereby reducing the adverse effects of the microstructure on cold deformation. On the other hand, a suitable amount of metastable β-phase with appropriate mechanical stability is obtained through strong air cooling starting at around 700℃, which allows it to undergo strain-induced transformation during cold deformation, resulting in phase transformation-induced plasticity and staged secondary work hardening, thereby improving the material's uniform deformation capacity and pre-fracture plasticity reserve.

[0026] The present invention will be further described below with reference to embodiments, comparative examples, and accompanying drawings. Unless otherwise specified, all samples were made of the same hot-rolled TC4 titanium alloy material, with an initial microstructure consisting of equiaxed primary α phase, acicular secondary α phase, and β phase. The gauge length of the room temperature tensile specimens was 25 mm. The work hardening rate was calculated based on the true stress-true strain curve and expressed as: θ = dσ / dε, where θ is the work hardening rate, σ is the true stress, and ε is the true strain.

[0027] Example 1 (1) Place the hot-rolled TC4 titanium alloy sample in a heat treatment furnace, heat it to 940 ℃, and hold it for 30 min; (2) After the heat preservation is completed, allow the sample to cool slowly with the furnace; (3) When the sample temperature drops to 700 °C, the sample is removed from the heat treatment furnace and immediately cooled to room temperature by strong air cooling. The strong air cooling is to use a fan to continuously blow air onto the sample surface, so that the sample is cooled to room temperature at a cooling rate higher than that of natural air cooling.

[0028] After the above treatment, the sample microstructure mainly consists of grain boundary α phase, intragranular lamellar α phase, and residual β phase. Compared with samples that were directly water-quenched, oil-quenched, or strongly air-cooled after holding at 940℃, the sample in this embodiment did not form a large number of needle-like α phases. ′ Martensite; compared with the sample that was furnace cooled to 540°C and then strongly air-cooled, the intracrystalline α phase lamellar layer in this embodiment did not undergo significant coarsening.

[0029] The yield strength of the sample in this embodiment was 755 MPa, the tensile strength was 801 MPa, the elongation was 19.0%, and the reduction of area was 64% after room temperature tensile testing.

[0030] from Figure 4The work hardening rate-true strain curve shows that the work hardening rate of the specimen in this embodiment decreases rapidly in the early stage of deformation, then rebounds significantly within a certain true strain range, and then decreases again, exhibiting a multi-stage change characteristic of "decrease-rebound-decrease". This change characteristic indicates that the specimen in this embodiment retains a metastable β phase with appropriate mechanical stability. In the early stage of deformation, the material mainly undergoes plastic deformation through dislocation slip; as the strain increases, when the critical stress or critical strain required for the metastable β phase to transform is reached, some metastable β phases undergo strain-induced transformation, thereby producing a phase transformation-induced plasticity effect and staged secondary work hardening. This staged secondary work hardening can compensate for the attenuation of dislocation work hardening capacity during deformation, delay strain localization and necking, and enable the specimen to obtain a higher elongation and reduction of area.

[0031] Therefore, the excellent cold working performance of this embodiment does not simply originate from the multiphase structure composed of grain boundary α phase, intragranular lamellar α phase, and residual β phase, nor is it due to the continuous decrease in work hardening rate throughout the deformation process. Rather, it originates from the synergistic effect of the following two aspects: First, the slow cooling stage of furnace cooling to 700°C suppresses the large number of needle-like α phases generated by direct strong air cooling at 940°C. ′ Martensite reduces strength; secondly, strong air cooling after 700℃ preserves the metastable β phase with appropriate mechanical stability, which improves plasticity through strain-induced transformation during cold deformation.

[0032] Comparative Example 1: Hot-rolled sample Room temperature tensile tests were conducted on hot-rolled TC4 titanium alloy specimens without pre-heat treatment. The microstructure of the hot-rolled specimens mainly consisted of equiaxed primary α phase, acicular secondary α phase, and β phase. Its yield strength was 753 MPa, tensile strength was 847 MPa, elongation was 18.0%, and reduction of area was 61%. The work hardening rate of the hot-rolled specimens generally showed a continuous decreasing trend with increasing strain, without the obvious staged rebound seen in Example 1, indicating that its β phase content or mechanical stability had not reached a state capable of producing a significant phase transformation-induced plasticity effect. Compared with the hot-rolled state, the yield strength of the specimens in Example 1 remained essentially unchanged, the tensile strength decreased from 847 MPa to 801 MPa, the elongation increased from 18.0% to 19.0%, and the reduction of area increased from 61% to 64%, indicating that Example 1 improved the cold deformation plasticity reserve of the material.

[0033] Comparative Example 2: Water-quenched sample Hot-rolled TC4 titanium alloy samples were heated to 940℃ and held for 30 min, followed immediately by water quenching. After water quenching, the high-temperature β phase underwent a rapid diffusionless transformation, and the microstructure of the samples mainly consisted of acicular α phases. ′Composed of martensite and β phase. Tensile testing at room temperature showed a yield strength of 769 MPa, a tensile strength of 953 MPa, an elongation of 13.0%, and a reduction of area of ​​51%. Numerous needle-like α-phase structures formed during water quenching... ′ Martensite significantly improved the tensile strength and cold deformation resistance of the specimens, while decreasing plasticity. Simultaneously, a large amount of the high-temperature β phase transformed into α during the cooling stage. ′ The martensite content and stability of the residual β phase at room temperature do not produce the same phase transformation-induced plasticity effect as in Example 1. Therefore, although the water-quenched specimen has high strength, its deformation resistance is large and its plasticity reserve is insufficient, making it unsuitable as the microstructure state before cold drawing.

[0034] Comparative Example 3: Oil-quenched sample Hot-rolled TC4 titanium alloy samples were heated to 940℃ and held for 30 min, followed immediately by oil quenching. After oil quenching, the microstructure of the samples mainly consisted of acicular α-structures. ′ Composed of martensite and β phase. Tensile testing at room temperature showed a yield strength of 732 MPa, a tensile strength of 897 MPa, an elongation of 9.5%, and a reduction of area of ​​26%. The oil-quenched specimen exhibited significantly lower elongation and reduction of area than Example 1, indicating that the needle-like α phase... ′ Martensitic structure has a significant adverse effect on cold deformation plasticity. Its residual β-phase content and mechanical stability are also insufficient to produce sufficient phase transformation-induced plasticity.

[0035] Comparative Example 4: Directly Forced Air-Cooled Sample Hot-rolled TC4 titanium alloy samples were heated to 940℃ and held for 30 min. After holding, they were directly cooled to room temperature using a strong airflow. After this treatment, the microstructure of the samples mainly consisted of acicular α-structures. ′ The sample consists of martensite, fine lamellar secondary α-phase, and β-phase. Room temperature tensile testing revealed a yield strength of 645 MPa, a tensile strength of 820 MPa, an elongation of 14.5%, and a reduction of area of ​​37%. The work hardening rate curve of the directly air-cooled sample showed a certain degree of decrease followed by a rebound, indicating the presence of a metastable β-phase capable of strain-induced transformation during room temperature deformation. However, due to the direct air-cooling from 940℃, needle-like α-phase still formed in the initial cooling stage. ′ Martensite. Acicular α ′ The proportions and distribution of martensite, secondary α-phase, and metastable β-phase were not optimal, and the adverse effects of the martensitic structure weakened the transformation-induced plasticity effect of the metastable β-phase. Therefore, its elongation and reduction of area were significantly lower than in Example 1.

[0036] This comparative example illustrates that while strong air cooling alone may yield some metastable β phases, it cannot simultaneously prevent needle-like α phases. ′Martensite formation can only be suppressed by combining front-stage furnace cooling with rear-stage forced air cooling. ′ The goal is to obtain martensite and metastable β phase.

[0037] Comparative Example 5: Naturally Air-Cooled Sample Hot-rolled TC4 titanium alloy samples were heated to 940℃ and held for 30 min, then naturally cooled to room temperature in air. After treatment, the microstructure of the samples mainly consisted of grain boundary α phase, intragranular lamellar α phase, and residual β phase. Tensile testing at room temperature showed a yield strength of 692 MPa, a tensile strength of 843 MPa, an elongation of 15.5%, and a reduction of area of ​​48%. The work hardening rate curve of the naturally air-cooled samples also showed a certain degree of decrease followed by a rebound, indicating the possible presence of metastable β phases capable of strain-induced transformation in the microstructure. However, due to the lower cooling rate of natural air cooling compared to forced air cooling, the residual β phase underwent further decomposition during cooling, and β-stable elements diffused and accumulated more fully, resulting in a less than optimal balance between the content and mechanical stability of the residual β phase. Therefore, its phase transformation-induced plasticity effect was weaker than in Example 1, and the final elongation and reduction of area were both lower than in Example 1.

[0038] Comparative Example 6: Samples cooled by forced air after furnace cooling to 540℃ Hot-rolled TC4 titanium alloy samples were heated to 940℃ and held for 30 min. After holding, the samples were cooled in the furnace to 540℃, then removed from the furnace and immediately cooled to room temperature by strong air. After treatment, the microstructure of the samples mainly consisted of grain boundary α phase, coarse lamellar α phase within the grains, and a small amount of residual β phase. Tensile testing at room temperature showed a yield strength of 681 MPa, a tensile strength of 783 MPa, an elongation of 12.5%, and a reduction of area of ​​30%. The work hardening rate curve of the samples also showed a characteristic of first decreasing and then increasing, indicating that a certain amount of metastable β phase capable of strain-induced transformation still exists in the microstructure. However, due to the continued furnace cooling to 540℃, the high-temperature β phase underwent further diffusion-type decomposition during cooling, the lamellae of the intragranular α phase became significantly coarser, and the content of residual β phase decreased. Simultaneously, the β-stabilizing elements in the remaining β phase were further enriched, improving the stability of some β phases.

[0039] Therefore, although the small amount of metastable β phase in the sample can still produce a certain degree of staged secondary work hardening, its phase transformation-induced plasticity is insufficient to offset the adverse effects caused by excessive coarsening of the intracrystalline α phase and the reduction in the number of residual β phases, ultimately leading to a significant decrease in elongation and reduction of area.

[0040] This comparison demonstrates that the furnace cooling termination temperature cannot be too low. Only by terminating furnace cooling in a suitable medium-temperature zone and switching to strong air cooling can the suppression of needle-like α-rays be achieved. ′The three aspects are martensite, avoiding excessive coarsening of the α phase, and obtaining an appropriate amount of metastable β phase.

[0041] Performance results obtained from Example 1 and Comparative Examples 1 to 6

[0042] The yield strength of the sample in Example 1 was 755 MPa, which is basically equivalent to the 753 MPa of the hot-rolled sample. The tensile strength of Example 1 decreased from 847 MPa in the hot-rolled state to 801 MPa, indicating that the overall deformation resistance in the subsequent plastic deformation stage was reduced. The elongation of Example 1 reached 19.0%, and the reduction of area reached 64%, both of which were the highest values ​​among all test groups, indicating that the process simultaneously improved the overall plasticity and local plasticity before fracture of the material.

[0043] Based on the microstructure and work hardening rate curve, it can be seen that the reason why Example 1 has the best performance is not simply because it obtains a microstructure composed of grain boundary α phase, intragranular lamellar α phase and residual β phase, nor simply because it reduces the work hardening rate, but because the following synergistic effect is achieved through a combination of furnace cooling to 700°C followed by strong air cooling: First, the furnace cooling stage after holding at 940℃ makes it easy for needle-like α-type structures to form when the material is slowly cooled directly. ′ The martensitic transformation zone promotes the precipitation of diffuse α phase and avoids the formation of a large number of needle-like α phases. ′ Martensite formation; Secondly, furnace cooling is terminated at 700℃ to prevent further coarsening of the α phase within the crystals and further decomposition of the residual β phase. Furthermore, the strong air cooling after 700℃ retains the residual β phase at a suitable cooling rate and keeps some of the β phase in a metastable state; Finally, the metastable β phase undergoes strain-induced transformation during subsequent cold deformation, resulting in phase transformation-induced plasticity and staged secondary work hardening, which delays strain localization, necking, and crack initiation.

[0044] Therefore, the heat treatment process of holding at 940℃ for 30 minutes, furnace cooling to 700℃, and then strong air cooling is suitable for needle-shaped α-type needles. ′ It achieves a good match between martensite suppression, α-phase morphology, metastable β-phase content, β-phase mechanical stability and plastic deformation capacity, making it suitable as a heat treatment process before cold drawing of TC4 titanium alloy wire.

Claims

1. A pre-heat treatment method for TC4 titanium alloy, characterized in that, Includes the following steps: a. Place the hot-rolled TC4 titanium alloy in a heat treatment furnace, heat the furnace to 930°C to 950°C, and hold for 20 to 40 minutes; b. After the heat treatment is completed, the TC4 titanium alloy in the heat treatment furnace is cooled to 680°C to 720°C. c. Subsequently, the TC4 titanium alloy was removed from the heat treatment furnace and cooled to room temperature by strong air.

2. The pre-heat treatment method for TC4 titanium alloy as described in claim 1, characterized in that: The hot-rolled TC4 titanium alloy is in the form of wire, coil, or bar.

3. The pre-heat treatment method for TC4 titanium alloy as described in claim 1, characterized in that: In step c, forced air cooling includes fan-assisted cooling, blower cooling, or compressed gas jet cooling.

4. The pre-heat treatment method for TC4 titanium alloy as described in any one of claims 1 to 3, characterized in that: In step a, the heat treatment furnace is heated to 940°C and held for 30 minutes.

5. The pre-heat treatment method for TC4 titanium alloy as described in claim 4, characterized in that: In step b, the TC4 titanium alloy in the heat treatment furnace is cooled to 700°C.

Citation Information

Patent Citations

  • Method for improving strength of TC4 titanium alloy wire

    CN120210703A